INNOVATIVE APPROACHES TO THE TEACHING OF FOREIGN LANGUAGES AT LEVELS B2 - C1 (FROM THE EXPERIENCE OF THE TEXTBOOK) - E. B. Yastrebova; D. A. Kryachkov (Vestnik MGIMO-Universiteta)
The article analyzes how professors and students of MGIMO-University’s School of International Relations perceive innovations in language teaching.As a synergy system, language teaching relies on selfdevelopment based to a great extent on innovations, which can be initiated either from the inside or from the outside. To identify the basic features of innovations in foreign language teaching, the authors conducted a survey of professors and students of the School of international Relations. The results suggest that for most respondents the main purpose of innovations in foreign language teaching and learning is to attain a significantly higher level of communicative competence, which is seen as feasible only if fundamentally new teaching materials and computer technologies are used. According to the survey, the success of innovations largely depends on their source (innovations ‘from the top’ and innovations ‘from the bottom’) and commitment on the part of professors and students to participate in them, the latter being often prompted by their discontent with the state of play. Innovations ‘from above’ tend to be more encompassing and affect the entire system of language education, whereas innovations ‘from the bottom concern the teaching process per se. Though the survey suggests that it is innovations ‘from the top’ that tend to be more successful, the authors conclude that language education as a synergy system adopts only non-shattering innovations that address its most vital needs, thus encouraging its sustainable development.